Informative value of whole-body magnetic resonance imaging with diffusion-weighted images for the detection of bone marrow infiltration in patients with multiple myeloma (literature review) - N. S. Lutsik; L. P. Mendeleeva; G. A. Yatsik (Онкогематология, 2022)
Magnetic resonance imaging (MRI) is increasingly being used to diagnose bone marrow lesions in patients with multiple myeloma (MM). Since 2014, the results of MRI have been included in the updated criteria of the International Myeloma Working Group. The presence of >1 bone marrow lesion larger than or equal to 5 mm on MRI is considered sufficient for the diagnosis of symptomatic MM, requiring initiation of treatment. MRI assessment of bone marrow is also possible with functional sequences such as diffusion-weighted imaging (DWI), which provide additional information about the bone marrow. This article provides an overview of the possibilities of MRI with anatomical sequences and with DWI for diagnosing, monitoring and evaluating the response to treatment in patients with MM. In patients with monoclonal gammopathy of undetermined significance and smoldering myeloma, in some cases, pathological changes in the bone marrow can be detected by MRI. The presence of >1 bone marrow lesion on MRI is a cut-off value as a prognostic factor for the progression of monoclonal gammopathy of undetermined significance or smoldering myeloma to symptomatic MM. In symptomatic MM, there are four patterns of bone marrow infiltration on MRI – focal, diffuse, “salt-and-pepper” infiltration, and combined diffuse and focal pattern, which have prognostic significance. Patients with diffuse pattern of infiltration on MRI had a 3-year overall survival of 35 % versus 92 % in patients with normal MRI bone marrow. During treatment of MM patients, residual bone marrow lesions are often identified on MRI. MRI residual bone marrow lesions increase the risk of MM relapse. In the group of patients who had residual bone marrow lesions on MRI on the 100th day after autologous hematopoietic stem cell transplant, 2-year progression-free survival was 50 % versus 89 % in patients without bone marrow lesions at the same time. The addition of DWI to the scan protocol helps to differentiate persistent focal bone marrow lesions that can lead to MM relapse after the treatment phase. Apparent diffusion coefficient is a quantitative indicator of DWI. MRI can serve as a valuable tool for assessing the treatment response in patients with MM.